Baseline sleep quality, stress and depressive symptoms and subsequent headache occurrence in a six-week prospective cohort study of patients with episodic migraine - Vgontzas, Angeliki (Headache, 2021)
BACKGROUND: Despite the high prevalence of sleep disturbance, stress, and depressive symptoms among patients with episodic migraine, there has been limited prospective research examining how these comorbid symptoms relate to future headache risk. METHODS: We conducted an a priori secondary analysis of a prospective cohort study of 98 adults with episodic migraine recruited through Harvard-affiliated medical centers and local college student clinics in Boston, MA. At baseline, participants completed validated questionnaires on sleep quality, stress, and depressive symptoms. Over the next six weeks, they recorded headaches on twice-daily diaries. We conducted time-to-event analyses to evaluate whether these baseline symptoms are associated with headache recurrence. RESULTS: At baseline, 45/98 (46%) participants had poor sleep quality, 51/98 (52%) reported moderate/high stress levels, and 18/98 (18%) had high depressive symptom scores. Over 4,406 person-days, we observed 823 discrete headaches. In multivariable models, the hazard ratios for headache recurrence were: 1.22 (95% CI 1.02, 1.46) for people with baseline poor sleep, 1.12 (95% CI 0.93, 1.35) for those with baseline moderate/high stress compared to lower levels, and 1.31 (95% CI 1.05, 1.65) for the combination of poor sleep and moderate/high stress compared to the combination of good sleep and low stress. There was no association between depression scores and headache risk. DISCUSSION: Among patients with episodic migraine, poor sleep was associated with a higher rate of headache recurrence over the next six weeks, especially among those with coexisting moderate/high stress.